Emotional closeness to maternal versus paternal lineages - Júnior, MS; Dunbar, RIM; Brito, R (American Psychological Association, 2014)
Kinship theory predicts that people will be more willing to engage, support, and, as a consequence, be more bonded with genetically close kin. Furthermore, 2 kin of the same degree may be treated differently depending on whether they are maternal or paternal. We here ask whether people are more likely to recall some relatives than others as a function of their relatedness and/or emotional closeness. People from 3 countries were asked to report their kin relations using the Social Network Questionnaire. We indexed recall by the order in which individuals were listed on the questionnaire. The results showed a consistent preference for maternal relatives over paternal relatives. Mothers, fathers, and siblings were typically listed in first, second, and third rank positions, respectively. Maternal kin also had the highest levels of emotional closeness, which decreased with listing order. Young respondents tended to list maternal relatives, and be emotionally closer to them, more frequently than older people. No differences were found with respect to respondent sex. The few differences across the samples may be attributed to cultural influences, but these were modest. Considering that maternal kin invest more time and resources in the mother’s offspring than paternal kin, we interpret the preferences for maternal kin as a psychological consequence of paternity uncertainty.